Why do people share knowledge in online social Q&A communities? - Li, Mengcheng (2017)
As there is increasing volume of knowledge with the development of technology and human intelligence, it is a fast and efficient way for individuals to get knowledge from others’ sharing. Therefore, it is of significant importance to understand why people are willing to share their knowledge and in this paper the context of online social Q&A communities are discussed. A measurement model is established to test variables from the perspectives of intrinsic motivation, extrinsic motivation, personal variables, members’ perceptions about the community, factors that may discourage knowledge contribution. 12 variables including reputation, expected associations, self-efficacy, norm of reciprocity, use of self-presentation, enjoying helping, attention, trust, identification/commitment, loss of knowledge power, codification effort and cyber-bullying have been discussed and analyzed to investigate their impacts on individual’s perceived knowledge contribution as well as the quantity and quality of their actual knowledge sharing behavior. Survey data and empirical data were collected and combined for analysis with 269 complete responses. In addition, individual differences including gender, age, duration, status, education and tenure are taken into consideration in the structural model using PLS technique. Interesting findings as well as theoretical and practical implications are discussed at last.